Intrarater reliability of cervical range of motion device among adults with and without chronic non-specific neck pain - Akhter, Saeed; Hamayun Zafar; Ashfaq Ahmad; Waqas Ahmed Farooqui (Journal of the Pakistan Medical Association, 2023)
Objectives: To evaluate the intrarater reliability of the cervical range of motion device among adults with and without chronic non-specific neck pain. Method: The analytical, cross-sectional study was conducted from January to March 2019 at the Sindh Institute of Physical Medicine and Rehabilitation, Karachi, and comprised healthy adults with no neck pain in the preceding 6 months in Group A, and adults of either gender with chronic non-specific neck pain for >3 months in Group B. The two groups were further divided into age groups 21-30 years, 31-40 years and 41-50 years. A cervical range of motion device was used to measure the range of flexion, extension, right and left lateral flexion and right and left rotation of all the subjects. The measurements were taken by a single tester on day-1 and day-3 to assess the intrarater reliability. Data was analysed using SPSS 26. Results: Of the 60 subjects, there were 30(50%) in each of the two groups. Within the groups, there were 10(33.3%) subjects in each of the 3 age subgroups. Overall, there were 27(45%) males and 33(55%) females. In Group A, the intraclass correlation coefficient values for all cervical ranges were between 0.81 and 0.99, whereas in Group B, the values ranged from 0.64 to 0.88. The intraclass correlation coefficient values yielded good to excellent agreement in both groups (>0.75) except for left lateral flexion in Group B (p=0.64), and all the values were statistically significant (p<0.05). Conclusion: There was good to excellent intrarater reliability of cervical range of motion device in adults with and without chronic non-specific neck pain. Key Words: Reliability, Range of motion, Spinal column, Non-specific neck pain.